Desain Kap Lampu dari Sampah Wadah Telur Berbahan Karton Menggunakan Teknik Komposit: Reduce egg container waste - Candra Davit Victory; Marcellino Aditya (Jurnal Desain Produk Nasional, 2025)
Eggs are one of the foodstuffs that many people consume as daily food. Consuming a lot of eggs and distributing eggs using cardboard or paper egg containers has an effect on the waste produced from this distribution, the waste produced includes inorganic waste. Inorganic waste includes waste that can cause environmental pollution. One way to reduce inorganic waste, especially cardboard egg containers, is by recycling it using a material exploration process. Exploration of safe materials to utilize cardboard egg container waste using composite techniques. The composite technique is carried out using mixed materials such as gelatin, glycerol and water as the main binder material. This design focuses on making a lampshade in the bedroom. This design concept is intended as a medium for lighting sleeping lamps in bedrooms and boarding houses. This design uses the SCAMPER method which is applied from the results of material exploration and the addition of support material, namely laminated bamboo as legs. The composite technique requires the right composition, namely 25g gelatin, 5g egg container, 1g glycerol and 100ml water or in a ratio of 5 : 1 : 0.2 : 10 to get a material that is strong, translucent to light and therefore suitable for use as a lampshade.